1973
DOI: 10.1128/iai.7.5.817-822.1973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lysozyme and Chitinase on the Spherules of Coccidioides immitis In Vitro

Abstract: Spherules of Coccidioides immitis strain Silveira produced in vitro were treated with chitinase and lysozyme. The walls of merthiolate-killed mature endosporulating spherules were degraded by chitinase (500 ug/ml) and by lysozyme (100 and 500 Ag/ml). Thus, as was visible through the light microscope, the spherule wall was reduced in thickness from 1 to 2 ,m to less than 0.5 ,m. The degradation was evident also by release of N-acetylglucosamine, three times as much N-acetylglucosamine being released by chitinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The presence of lymphocytes from immune animals in the macrophage culture resulted in enhanced fusion, as has been previously observed with N. asteroides (9), and in our investigation, fusion of the phagosomes and lysosomes correlated with the extent of fungicidal activity. Collins and Pappagianis found that lysozyme has a lethal effect in vitro on spherules (8); however, lysozyme secretion by macrophages apparently is not altered by activation of macrophages (7). Thus, future experimentation is required to determine how C. immitis is killed and to define the mechanism whereby lymphocytes activate macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of lymphocytes from immune animals in the macrophage culture resulted in enhanced fusion, as has been previously observed with N. asteroides (9), and in our investigation, fusion of the phagosomes and lysosomes correlated with the extent of fungicidal activity. Collins and Pappagianis found that lysozyme has a lethal effect in vitro on spherules (8); however, lysozyme secretion by macrophages apparently is not altered by activation of macrophages (7). Thus, future experimentation is required to determine how C. immitis is killed and to define the mechanism whereby lymphocytes activate macrophages.…”
Section: Discussionmentioning
confidence: 99%